Technological factors affecting knowledge sharing among academic staff in selected Malaysian higher educational institutions and the effect on performance - Supar, Norizah (International Foundation for Research and Development (IFDR), 2012)
The objective of this study is to expand our understanding of the factors that affect knowledge sharing among academic staff in Malaysian higher academic institutions. Although previous research has identified several factors that affect knowledge sharing, further research needs to be carried out to ascertain factors that affect knowledge sharing, in particular among higher academic institutions in Malaysia. Its relevance to higher academic institutions is especially pertinent considering that being a center of learning, a higher level of knowledge sharing among the teaching staff could bring about an increased level of productivity or performance and satisfaction in the workplace. The outcome of this study will enable further understanding on knowledge sharing behavior of academic staff and may therefore contribute towards successful implementation of knowledge sharing as part of organizational knowledge management initiatives. Based on non-random, criterion, purposive sampling, three higher academic institutions from the Klang Valley area were selected to be included in the study. Findings from 194 respondents indicated that the technological factors of distributed model and presence of IT for knowledge sharing are positively related to knowledge sharing and that knowledge sharing is positively related to performance.